Strategi Dinas Tenaga Kerja Dalam Menanggulangi Pengangguran Di Kota Samarinda - Febri Tri Ananda Putera; Muhammad Jamal Amin (Jurnal Ilmu Pemerintahan, 2024)
The strategy carried out by the Samarinda City Manpower Department in overcoming unemployment refers to the Samarinda City Manpower Department's Strategic Plan (Renstra) for 2021-2026. The Samarinda City Manpower Service aims to increase employment opportunities with the target of reducing the level of open unemployment. In achieving this goal, the Samarinda City Manpower Office uses three strategies. First, increase the competitiveness of the workforce and create new jobs by carrying out Job Training and Workforce Productivity programs. Second, job expansion through data collection on job seekers which will later be distributed to companies that need workers through inter-work programs. Third, the Samarinda City Manpower Office brings together job seekers and labor users or companies directly with the aim of facilitating job seekers to get jobs according to their talents, interests and abilities through a job fair/job fair program.